Oxygen transfer to cassava starch solutions in an aerated, well-mixed bioreactor: Experimental and mass transfer studies - Saptoro, Agus; Ting, M.; Liew, Emily (Springer New York LLC, 2014)
Experimental and mass transfer studies of oxygen transfer to cassava starch solution in an aerated, well-mixed bioreactor of 2 L have been carried out. The volumetric mass transfer coefficient was estimated and parametric studies were performed to study the effect of process variables of stirring rate, aeration rate, concentration of starch and temperature on the volumetric mass transfer coefficient. From the experimental results, it is evident that the first two and the last variables are directly proportional to the volumetric mass transfer coefficient. However, the volumetric mass transfer coefficient is inversely proportional to the concentration of the starch. Also, the saturation dissolved oxygen concentration is greatly affected by temperature and starch solution concentration. Whereas, stirring and aeration rates have neutral impacts on saturation dissolved oxygen concentration. Simulated data generated from obtained volumetric mass transfer coefficient agrees well with the experimental data, which indicates the accuracy of the coefficient.